Partial nitritation ANAMMOX in submerged attached growth bioreactors with smart aeration at 20 °C. Issue 1 (19th November 2014) - Shannon, James M.; Hauser, Lee W.; Liu, Xikun; Parkin, Gene F.; Mattes, Timothy E.; Just, Craig L.
Abstract : Smart-aerated submerged attached growth bioreactors perform partial nitritation ANAMMOX at 20 °C. Abstract : Submerged attached growth bioreactors (SAGBs) were operated at 20° C for 30 weeks in smart-aerated, partial nitritation ANAMMOX mode and in a timer-controlled, cyclic aeration mode. The smart-aerated SAGBs removed 48–53% of total nitrogen (TN) compared to 45% for SAGBs with timed aeration. Low dissolved oxygen concentrations and cyclic pH patterns in the smart-aerated SAGBs suggested conditions favorable to partial nitritation ANAMMOX and stoichiometrically-derived and numerically modeled estimations attributed 63–68% and 14–44% of TN removal to partial nitritation ANAMMOX in these bioreactors, respectively. Ammonia removals of 36–67% in the smart-aerated SAGBs, with measured oxygen and organic carbon limitations, further suggest partial nitritation ANAMMOX. The smart-aerated SAGBs required substantially less aeration to achieve TN removals similar to SAGBs with timer-controlled aeration. Genomic DNA testing confirmed that the dominant ANAMMOX seed bacteria, received from a treatment plant utilizing the DEMON® sidestream deammonification process, was a Candidatus Brocadia sp. (of the Planctomycetales order). The DNA from these bacteria was also present in the SAGBs at the conclusion of the study providing evidence for attached growth and limited biomass washout.